Given:
y - 4 = -4/5 (x - 1)
We need to find the x and y-intercept of the above.
To find the x-intercept, substitute y=0 into the equation and solve for x.
That is;
0 - 4 = -4/5 (x -1)
Mutiply both-side by -5/4
![-4*-(5)/(4)=-(5)/(4)*-(4)/(5)(x-1)](https://img.qammunity.org/2023/formulas/mathematics/college/1ad1nrj11x8a3jmerxeo7qfyoby8kbm70i.png)
5 = x - 1
Add 1 to both-side of the equation.
5 + 1 = x
6=x
x=6
Hence, the x-intercept is (6, 0).
Next, is to find the y-intercept.
Substitute x=0 and solve for y.
y - 4 = -4/5 (0 - 1)
y - 4 = 4/5
Add 4 to both-side of the equation.
y = 4/5 + 4
![y=(4+20)/(5)=(24)/(5)=4.8](https://img.qammunity.org/2023/formulas/mathematics/college/o1ehajh4bg5xwtvy3gg2q0d6demdn23a4z.png)
The y-intercept is ( 0, 4.8)
Attached below is the graph of the equation: